Access to care for childhood cancers in India: perspectives of health care providers and the implications for universal health coverage - Neha Faruqui; Sarah Bernays; Alexandra Martiniuk; Seye Abimbola; Ramandeep Arora; Jennifer Lowe; Avram Denburg; Rohina Joshi (BMC Public Health, 2020)
Abstract Background There are multiple barriers impeding access to childhood cancer care in the Indian health system. Understanding what the barriers are, how various stakeholders perceive these barriers and what influences their perceptions are essential in improving access to care, thereby contributing towards achieving Universal Health Coverage (UHC). This study aims to explore the challenges for accessing childhood cancer care through health care provider perspectives in India. Methods This study was conducted in 7 tertiary cancer hospitals (3 public, 3 private and 1 charitable trust hospital) across Delhi and Hyderabad. We recruited 27 healthcare providers involved in childhood cancer care. Semi-structured interviews were audio recorded after obtaining informed consent. A thematic and inductive approach to content analysis was conducted and organised using NVivo 11 software. Results Participants described a constellation of interconnected barriers to accessing care such as insufficient infrastructure and supportive care, patient knowledge and awareness, sociocultural beliefs, and weak referral pathways. However, these barriers were reflected upon differently based on participant perception through three key influences: 1) the type of hospital setting: public hospitals constituted more barriers such as patient navigation issues and inadequate health workforce, whereas charitable trust and private hospitals were better equipped to provide services. 2) the participant’s cadre: the nature of the participant’s role meant a different degree of exposure to the challenges families faced, where for example, social workers provided more in-depth accounts of barriers from their day-to-day interactions with families, compared to oncologists. 3) individual perceptions within cadres: regardless of the hospital setting or cadre, participants expressed individual varied opinions of barriers such as acceptance of delay and recognition of stakeholder accountabilities, where governance was a major issue. These influences alluded to not only tangible and structural barriers but also intangible barriers which are part of service provision and stakeholder relationships. Conclusion Although participants acknowledged that accessing childhood cancer care in India is limited by several barriers, perceptions of these barriers varied. Our findings illustrate that health care provider perceptions are shaped by their experiences, interests and standpoints, which are useful towards informing policy for childhood cancers within UHC.